STRATEGI HUMAS BERBASIS PARTISIPASI ORANG TUA DALAM MENINGKATKAN LAYANAN PENDIDIKAN - A. Sa’dullah, A. Sa’dullah (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
The aim of this research is to identify concrete strategies to increase parent participation in school activities in the educational process. Examining various approaches used by educational institutions to interact and collaborate with parents. The data collection techniques used by the author are observation and interviews. The interview informants were the school principal, Deputy Head of Curriculum and teachers. The data analysis used uses Miles and Huberman analysis, namely data reduction, data presentation and verification. This research uses several data validity techniques, namely triangulation, peer depriving (talking with other people). The results of research on public relations strategies in improving educational services are. steps taken with a sociological approach, Social Responsibility Strategy, Cooperation Strategy, Coordinative and Integrative Strategy. By taking several steps, including forming a school committee, carrying out open communication between the school and parents, holding parent and teacher meetings, using digital tools as a communication tool, workshops and training. The form of educational services provided at MA Miftahul Ulum is the implementation of a curriculum that meets needs, teaching and learning activities, evaluation and assessment, guidance and counseling for students, implementation of extracurricular activities, moral and citizenship education, character development. The level of service provided by MA Miftahul Ulum and the level of satisfaction of students and parents are very high